Ten Years of Evolving Edupreneurship Study: A Systematic Literature Review - Pradana, Mahendra Arya Wisnu; Aniek Hindrayani; Sangka, Khresna Bayu (Universitas Hamzanwadi, 2026)
Edupreneurship research has shown a relatively increasing publication trend over the past decade, although the cumulative volume remains limited. This study aims to map the development of edupreneurship research, identify research gaps, and formulate future research agenda recommendations using the Theory, Context, and Methodology (TCM) framework. The study applies a Systematic Literature Review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol on Scopus-indexed journal articles. The selection process uses strict inclusion and exclusion criteria, while data are analyzed descriptively and thematically. The findings reveal an increasing annual publication trend, geographically concentrated research contexts, dominance of quantitative survey methods, limited use of explicit theories, and concentration of publications in high-reputation journals. Wordcloud analysis indicates a diversity of keywords that has not been fully explored in broader contexts. The implications emphasize the need to strengthen theoretical foundations, expand cross-national and cross-disciplinary contexts, and diversify methodological approaches to support more integrated and sustainable edupreneurship research.